The expert patient's contribution to the empowerment of people with diabetes mellitus - Delmo de Carvalho Alencar; Ana Maria Parente Garcia Alencar; Aline Raquel de Sousa Ibiapina; Lany Leide de Castro Rocha Campelo; João Cruz Neto; Paulo Roberto Vasconcellos-Silva (Rev Rene)
Objective: to uncover the contributions of specialist patients to the empowerment of people with diabetes mellitus. Methods: a qualitative study comprising three open virtual communities with public posts in Portuguese, aimed at discussing diabetes mellitus. The nuclei of meaning were identified through a word cloud, with mutual checking between three researchers using content analysis. Results: the interactions showed concern about the clinical dimension of the disease and the welcoming nature of suffering and anguish. It was also observed that living with diabetes provides knowledge about the disease, making these people propagators of knowledge and ensuring their participation in the treatment process. Furthermore, the dialogues provided by the online environment can contribute to health promotion, facilitating understanding of aspects inherent to diabetes. Conclusion: specialist patients are willing to answer questions based on the knowledge they have acquired through the experience of becoming ill, supporting their recommendations in the care and recommendations received during treatment. Contributions to practice: it is hoped that the results can contribute to the recognition and appreciation of new approaches to health promotion and self-care for people with diabetes, such as virtual communities.